The association of quality, risk, sacrifice, satisfaction and loyalty at the destination level: a structural model - Hossain, Enayet; Quaddus, Mohammed; Shanka, Tekle (Cognizant Communication Corporation, 2015)
The main purpose of this study was to explore empirically the association of quality, risk, sacrifice, satisfaction, and loyalty. Initially a conceptual model was proposed cultivating literature and then contextualized via field study. The analysis was done based on 602 samples collected from Cox’s Bazar, Bangladesh, using a Likert scale. The Partial Least Square-based Structure Equation Modeling approach was used for data analysis. The outcome presented a strong association among the constructs. This study demonstrates an important contribution to the body of knowledge in the area of tourism destinations’ management and marketing, and suggests important implications to both practitioners and academics.